Projektiranje enoetažnih armiranobetonskih montažnih hal po novem Evrokodu 8 - Isaković, Tatjana (Gradbeni vestnik, 2025)
The article provides an overview of the steps and outcomes of the force-based seismic design for a broad range of singlestory precast reinforced concrete buildings according to the second generation of Eurocode 8. The criterion defining the crosssectional dimensions of the columns was the 2% drift limitation. Buildings were designed considering a behaviour factor of q = 3 and an effective stiffness equal to 50% of the stiffness corresponding to the gross cross-section. The seismic response of the analysed buildings was evaluated using nonlinear pushover analysis (N2 method). It was found that the chord rotations of the columns were roughly double the value accounted for in the design. The second-order effects were also unexpectedly large, particularly in taller columns, where they exceeded permissible limits. The main causes for the substantial discrepancies between elastic and nonlinear analysis were an arbitrarily chosen behaviour factor q and an arbitrarily reduced effective stiffness, which were improperly aligned. The effective stiffness in the elastic analysis was nearly twice as high as observed in the nonlinear analysis. A comprehensive review of the differences between elastic and nonlinear analysis, along with a design method to address these gaps, is given in the accompanying article.
Keywords: enoetažne armiranobetonske montažne hale; Evrokod 8 druge generacije; force-based design; nelinearna potresna analiza; nonlinear seismic analysis; projektiranje po metodi sil; projektiranje za vpliv potresne obtežbe; second generation of Eurocode 8; seismic design; single-story precast reinforced concrete buildings